Handbook of plant virology - Khan, Jawaid A (Heritage, 2007)
A comprehensive guide to the terms and expressions commonly used in the study of plant virology, complete with descriptions of plant virus families down to the generic level. Rather than simply listing term in alphabetical order, Handbook of Plant Virology links each term to related terms within a theme and adds commentary from authors whose specific expertise adds additional dimensions to the topics. The result is an invaluable resource for research workers, educators, and students working in plant virology and pathology, crop protection, molecular biology, and plant breeding.